The value of the expression [tex]5c^{3} -6c\sqrt{-2c}[/tex] at c = -5 is [tex]5(-125 +6\sqrt{10})[/tex] .
An algebraic expression is an expression having constant and variable joined with algebraic operation(+,-,×,÷).
For Example , 2c+5x+6 is an algebraic expression.
In the given expression
[tex]=5c^{3} -6c\sqrt{-2c}[/tex]
Substituting the value of c = -5 .
We get ;
[tex]=5(-5)^{3} -6(-5)\sqrt{-2(-5)}[/tex]
[tex]=5(-125) +30\sqrt{-2(-5)}\\ \\ =-625 +30\sqrt{10}[/tex]
taking 5 common from both the terms
[tex]=5(-125 +6\sqrt{10})[/tex]
Therefore , the value of the expression [tex]5c^{3} -6c\sqrt{-2c}[/tex] is [tex]5(-125 +6\sqrt{10})[/tex].
Learn more about Simplification here https://brainly.com/question/13863650
#SPJ4